The inhibition of tumor protein p53 by microRNA-151a-3p induced cell proliferation, migration and invasion in nasopharyngeal carcinoma. Issue 10 (21st October 2019) - Liu, Haibin; Cheng, Yin; Xu, Yaping; Xu, He; Lin, Zheng; Fan, Jingping; Lang, Juntian
Abstract: A close relation between microRNA-151a-3p (miR-151a-3p) and nasopharyngeal carcinoma (NPC) has been reported, however, the molecular mechanism is still unclear. The aim of the present study was to explore the mechanism in the promotion of miR-151a-3p to NPC progression. The levels of miR-151-3p in several NPC cell lines were detected in order to screen an experimental cell line. MiR-151a-3p mimic and inhibitor were constructed and transfected into 5-8F cells and cell proliferation were detected by Cell Counting Kit-8 (CCK-8). The apoptosis rate, cell migration and invasion were determined by flow cytometry, wound healing and Transwell assays. The predicted target was further verified by luciferase reporter assay. Real-time quantification-PCR and Western blot were carried out for mRNA and protein level analysis. Tumor protein p53 was co-transfected to verify the functions of miR-151a-3p. The miR-151a-3p level in NPC tissues was much higher than that in adjacent tissues. After transfecting cells with miR-151a-3p mimic, the cell proliferation and patients' survival rate were much increased, and this was accompanied by the increase in B-cell lymphoma 2 (Bcl-2) and decreases in Bax and cleaved caspase-3 ( P <0.01). Moreover, the migration rate and number of invaded cells were also remarkably increased, however, the miR-151a-3p inhibitor had opposite effects on the 5-8F cells. Noticeably, p53 was revealed as a potential target of miR-151a-3p. Co-transfection of P53 could partially reverse the promotive effects of miR-151a-3p on NPC cell progression. Our data indicated that blocking p53 expression and mediated signal pathways contribute to the positive effects of miR-151a-3p on NPC cell proliferation, migration and invasion.